Isolation, Characterization, and Differentiation Potential of Canine Adipose-Derived Stem Cells - N. M. Vieira; V. Brandalise; E. Zucconi; M. Secco; B. E. Strauss; M. Zatz Ph.D. (Cell Transplantation, 2010)
Adipose tissue may represent a potential source of adult stem cells for tissue engineering applications in veterinary medicine. It can be obtained in large quantities, under local anesthesia, and with minimal discomfort. In this study, canine adipose tissue was obtained by biopsy from subcutaneous adipose tissue or by suction-assisted lipectomy (i.e., liposuction). Adipose tissue was processed to obtain a fibroblast-like population of cells similar to human adipose-derived stem cells (hASCs). These canine adipose-derived stem cells (cASCs) can be maintained in vitro for extended periods with stable population doubling and low levels of senescence. Immunofluorescence and flow cytometry show that the majority of cASCs are of mesodermal or mesenchymal origin. cASCs are able to differentiate in vitro into adipogenic, chondrogenic, myogenic, and osteogenic cells in the presence of lineage-specific induction factors. In conclusion, like human lipoaspirate, canine adipose tissue may also contain multipotent cells and represent an important stem cell source both for veterinary cell therapy as well as preclinical studies.